Giant magneto–electric coupling in 100 nm thick Co capped by ZnO nanorods. Issue 3 (3rd January 2018) - Vinai, Giovanni; Ressel, Barbara; Torelli, Piero; Loi, Federico; Gobaut, Benoit; Ciancio, Regina; Casarin, Barbara; Caretta, Antonio; Capasso, Luca; Parmigiani, Fulvio; Cugini, Francesco; Solzi, Massimo; et al.
Abstract : Giant strain-driven magnetoelectric coupling of Co/ZnO nanorods. Under ±2 V, the coercivity is reversibly reduced of a factor 5. Abstract : Here we report a giant, completely reversible magneto–electric coupling of 100 nm polycrystalline Co layer in contact with ZnO nanorods. When the sample is under an applied bias of ±2 V, the Co magnetic coercivity is reduced by a factor 5 from the un-poled case, with additionally a reduction of total magnetic moment in Co. Taking into account the chemical properties of ZnO nanorods measured by X-rays absorption near edge spectroscopy under bias, we conclude that these macroscopic effects on the magnetic response of the Co layer are due to the microstructure and the strong strain-driven magneto–electric coupling induced by the ZnO nanorods, whose nanostructuration maximizes the piezoelectric response under bias.